Healthcare Reforms in the US: A Multi-Billion Opportunity for Indian Firms - K. T., Thomas; Sakthi Vel, Dr. R. (Prabandhan: Indian Journal of Management, 2011)
The US health care industry is a complex entity with significant contrasts. Despite its leadership position in health care spending and medical research, over 45 million of the US population continue to be uninsured and cannot afford even basic medical care. To understand this paradox, one needs to take a look at the history of health care in the US. As early as in the 1920’s, US hospitals evolved into modern scientific institutions and along with this development came the beginning of health insurance, as a prepaid hospital plan, for covering sickness. This model was quickly embraced by the large workforce based organizations such as the auto and the railroad companies and employer sponsored health insurance plans became the de facto health benefit operating model in the US. During the 1960’s, as medical research began to cover a range of illnesses, cost of medical care increased, thereby making health insurance also unaffordable to the public. To address this, the US government created the Medicare and Medicaid social programs in 1965. Medicare extended health coverage to almost all Americans aged 65 or older and Medicaid provided access to health care services for low income and poor persons and people with disabilities.